2021
DOI: 10.30919/esmm5f458
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Applications of Phase Change Materials (PCMs) and PCMs-based Technologies

Abstract: It is necessary to develop new technologies for energy storage and use of renewable energy to improve energy efficiency. Phase change materials (PCMs) are a family of energy storage materials that are among one of the most suitable materials for storing and effectively utilizing renewable thermal energy. PCM-based latent heat storage (LHS) is more advantageous than sensible energy storage because of the high storage energy density per unit volume/mass and the smaller temperature difference between storing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 172 publications
0
17
0
Order By: Relevance
“…In recent years, the environmental deterioration and the huge depletion of fossil fuels have expedited the development of clean and renewable energy sources. Electrochemical energy storage devices are essential for the development of renewable energy system. This is because most of those renewable energy sources (i.e., solar, wind, hydro energy, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the environmental deterioration and the huge depletion of fossil fuels have expedited the development of clean and renewable energy sources. Electrochemical energy storage devices are essential for the development of renewable energy system. This is because most of those renewable energy sources (i.e., solar, wind, hydro energy, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, organic PCMs (OPCMs) distinguish for low supercooling, ignorable phase change, nontoxicity, high energy capacity and chemical stability, exhibiting great potential in practical implements. [15][16][17] In this regard, we will only discuss shape-stabilized PCMs (SSPCMs) based on OPCMs in this review. For the SSPCMs, multiple energy forms such as electricity, magneticity and solar energy etc.…”
Section: Introductionmentioning
confidence: 99%
“…The use of PCMs in laminated composite structures has also made some advances recently [24]. Based on the recent review articles on PCM technologies, it can be argued that the development of form-stable, environmentally friendly organic PCMs modified with certain nanomaterials for increased thermal conductivity and structural stability is gaining high popularity among researchers [25][26][27]. Recent studies have found that combining metals with PCMs can significantly enhance heat storage performance due to much higher heat transfer coefficient of metals causing efficient heat transport.…”
Section: Introductionmentioning
confidence: 99%